General slavic terminology: main trends of study - Ivashchenko, V.L.; Turovska, L.V.; Kazymyrova, I.A.; Yatsenko, N.O. (Термінологічний вісник, 2013)
The paper attempts to analyze main paradigm, aspectual, cross-paradigm, cross-aspectual and cross-disciplinary trends of study of the general Slavic terminology development in the late XX – early XXI centuries. Fundamental papers of Russian, Ukrainian, Belorussian, Polish, Czech, Bulgarian, Slovakian and Slovenian scholars are systematized according to the existing trends in the field of terminology. Зроблено спробу проаналізувати основні парадигмальні, аспектуальні, кроспарадигмальні, крос-аспектуальні та крос-дисциплінарні дослідницькі напрями розвитку загального слов’янського термінознавства кінця ХХ – початку ХХІ століття. Відповідно до напрямів систематизовано фундаментальні праці російських, українських, білоруських, польських, чеських, болгарських, словацьких, словенських дослідників у царині термінознавства.